Image compression study and socket-based transmission - Shen, Feng. (2008)
An easy-to-use prototyped software package has been developed based on the client-server approach to enable the transmission of images through various networks, including LAN, WAN, or Internet. Various features are provided for file searching, compressing and transmitting images within an acceptable time frame. The latest JPEG2000 technique for image compression/decompression is implemented in this development. The software is developed using Microsoft VC++ 6.0 compiler and Microsoft Foundation Class (MFC) is heavily used to avoid low-level network control and to speed up the development process. A simple visual user interface has also been designed to demonstrate the available facilities and the on-going communication process.